Glucose Intake Alters Expression of Neuropeptides Derived from Proopiomelanocortin in the Lateral Hypothalamus and the Nucleus Accumbens in Fructose Preference Rats - Guangfa Jiao; Guozhong Zhang; Haiying Wang; Weilin Zhao; Yanwei Cui; Yongjing Liu; Feng Gao; Fang Yuan; Yi Zhang (Neural Plasticity)
To study the neuroendocrine mechanism of sugar preference, we investigated the role of glucose feeding in the regulation of expression levels of neuropeptides derived from proopiomelanocortin (POMC) in the lateral hypothalamus (LH) and nucleus accumbens (NAc) in fructose preference rats. Fructose preference rats were induced by using the lithium chloride backward conditioning procedure. The fructose preference was confirmed by the two-bottle test. The drinking behavior of rats was assessed by the fructose concentration gradient test. The preference of 10% glucose or 0.1% saccharine was assessed, and the expression levels of neuropeptides derived from POMC in the LH and the NAc in fructose preference rats were measured by Western blot analysis. Fructose preference rats displayed a greater fructose preference than control rats. Furthermore, fructose preference rats preferred glucose solution rather than saccharine solution, while control rats preferred saccharine solution rather than glucose solution. The expression levels of neuropeptides derived from POMC in the LH and the NAc were changed by glucose but not saccharine intake. In summary, the data suggests that glucose intake increases the expression of neuropeptides derived from POMC in the LH and the NAc in fructose preference rats.